White College Students’ Racial Prejudice and Perceptions of Racial Hate Crime - Woo, Bongki (Journal of interpersonal violence, 2022)
This study investigated how racial prejudice influences White college students? perceptions of hate crime. We also examined the moderating effects of the race of the victim of hate crimes and the absence of hate crime laws. Our sample included 581 White students in a predominantly White university located in a state that does not have a hate crime law. The study was set up in a 2 (race of the victim and the perpetrator) ? 3 (level of assault) factorial design. Participants rated their perceptions of three scenarios (i.e., non-racially biased simple assault, racially biased simple assault, and racially biased aggravated assault). The dependent variables were perceptions of hate crime and willingness to report. The key independent variable was participants? level of racial prejudice. The moderators included race of the victim in each scenario and whether participants? state of origin has a hate crime law. Results suggest that higher levels of modern racism were associated with lower perceptions of hate crime and lower willingness to report racially biased simple and aggravated hate crime. When the victim was White, participants with higher levels of racial prejudice were more likely to perceive a hate crime and more willing to report it. The opposite was true when the victim was Black. The absence of state hate crime laws and race of victim were significant moderators. Our study suggests that racial prejudice is associated with lower perceptions of hate crime and willingness to report. Furthermore, the moderating effect of the race of victims provides insights on how racial prejudice can lead to a differential perception of hate crime, depending on whether one?s racial in-group is targeted. Our findings also highlight the importance of having state-level hate crime laws to mitigate the linkage between modern racism and perceptions of hate crime.